Unraveling Spatial Dynamics of Urban Complexity Between Land Use Patterns and Travel Behavior Using Structural Equation Modeling - Abdulla Al Kafy; Md. Abdul Fattah; Mahir Shahrier; Hamad Ahmed Altuwaijri (Complexity)
Rapid urbanization and inadequate transportation infrastructure in developing countries have led to complex, unsustainable travel patterns and adverse environmental impacts. This study employs structural equation modeling (SEM) to explore the interplay between land use patterns and travel behavior in Rajshahi, Bangladesh. Analyzing data from 1298 respondents, we uncovered intricate relationships between sociodemographic, economic, and spatial factors. The SEM revealed that economic characteristics had the highest total effect (0.674) on travel behavior, followed by land use (0.521). Notably, accessibility negatively correlated with economic (−0.70) and sociodemographic factors (−0.91). The residential environment emerged as the most significant land use indicator, with a weight of 1.820. Our analysis found that 31% of trips used easy bikes, while 23% were on foot. The employment rate positively impacted economic characteristics (1.270), despite the considerable weight of total household income (0.874). Key findings indicate that economic characteristics and land use patterns are the primary drivers of travel behavior, highlighting the need for integrated urban planning. This study provides a nuanced understanding of urban complexity, offering valuable insights for sustainable transportation planning in developing cities. By elucidating the nonlinear interactions between various urban elements, our research contributes to the growing field of complex systems analysis in urban transportation contexts.